Sodium Bicarbonate Sub-Diaphragmatic Irrigation Relieves Shoulder Pain After Total Laparoscopic Hysterectomy: A Randomized Controlled Trial - Liu L (Dove Medical Press, 2021)
Li Liu,1,* Tian Xia,2,* Haiyan Ji,1 Yaxin Guo,1 Junfeng Liu,1 Liping Du,1 Daoyun Lei,3 Chao Han,1 Tieliang Ma4 1Department of Anesthesiology, The Affiliated Yixing Hospital of Jiangsu University, Yixing, Jiangsu, People’s Republic of China; 2Department of Gynaecology, The Affiliated Yixing Hospital of Jiangsu University, Yixing, Jiangsu, People’s Republic of China; 3Department of Anesthesiology, Zhongda Hospital Southeast University, Nanjing, Jiangsu, People’s Republic of China; 4Central Laboratory, The Affiliated Yixing Hospital of Jiangsu University, Yixing, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chao Han Tel +86 0510-87921000 Email staff940@yxph.com.telStudy Objective: To determine whether sub-diaphragmatic irrigation with sodium bicarbonate would relieve post-laparoscopic shoulder pain (PLSP) after total laparoscopic hysterectomy.Design: Randomized double-blinded trial.Setting: Teaching hospital.Patients: Seventy patients undergoing total laparoscopic hysterectomy (TLH) for benign indications.Intervention: We randomly allocated patients to intervention or control groups where sodium bicarbonate containing flushing liquid or normal saline was irrigated sub-diaphragm before sewing.Measurement & Main Results: The primary outcome was PLSP following surgery measured by a numerical rating scale (NRS) (0 = no pain; 10 = worst pain imaginable). Secondary outcomes were abdominal incisional and visceral pain, analgesic use, and sodium bicarbonate related side effects. The incidence of PLSP in intervention group was significantly lower than that in control group (P < 0.05). Contrarily, incisional and visceral pain was similar in both groups (P = 0.1). The consumption of rescue analgesics in the intervention group was lower than that in the control group. Side effects were comparable in both study groups.Conclusion: Sub-diaphragmatic irrigation with sodium bicarbonate could effectively reduce shoulder pain, but not abdominal incisional and visceral pain, in patients undergoing TLH without an increase in side effects.Registration information: Clinical trial registry number: http://www.chictr.org.cn/ (ChiCTR2100041765)Registration findings: http://www.chictr.org.cn/showproj.aspx?proj=66721 Link to clinical trial page and data repository: http://www.medresman.org.cn/pub/cn/proj/projectshshow.aspx?proj=2992Keywords: total laparoscopic hysterectomy, post-laparoscopic shoulder pain, sodium bicarbonate